Chronic disorders with episodic manifestations: focus on epilepsy and migraine - Haut, Sheryl R (2006)
Epilepsy and migraine are chronic neurological disorders with episodic manifestations that are commonly treated in neurological practice and frequently occur together. In this review we examine similarities and contrasts between these disorders, with focus on epidemiology and classification, temporal coincidence, triggers, and mechanistically based therapeutic overlap. This investigation draws attention to unique aspects of both epilepsy and migraine, while identifying areas of crossover in which each specialty could benefit from the experience of the other.